2016
DOI: 10.14411/fp.2016.031
|View full text |Cite
|
Sign up to set email alerts
|

Blood flukes of Asiatic softshell turtles: revision of Coeuritrema Mehra, 1933 (Digenea: Schistosomatoidea) and a new species infecting Chinese softshell turtles, Pelodiscus sinensis (Trionychidae), from Vietnam

Abstract: Coeuritrema Mehra, 1933, previously regarded as a junior subjective synonym of Hapalorhynchus Stunkard, 1922, herein is revised to include Coeuritrema lyssimus Mehra, 1933 (type species), Coeuritrema rugatus (Brooks et Sullivan, 1981) comb. n., and Coeuritrema platti Roberts et Bullard sp. n. These genera are morphologically similar by having a ventral sucker, non-fused caeca, two testes, a pre-testicular cirrus sac, an intertesticular ovary, and a common genital pore that opens dorsally and in the sinistral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…During July 2016, the viscera of 5 matamatas (C. fimbriata) from the Bele´n Market (3845 0 32.08 00 S, 73814 0 53.15 00 W), Iquitos, Peru (Amazon River), were examined opportunistically for blood fluke infections following previously published procedures (Roberts et al, 2016a(Roberts et al, , 2016b(Roberts et al, , 2016c(Roberts et al, , 2018a(Roberts et al, , 2018b(Roberts et al, , 2019 observed microscopically prior to fixation, fixed in 5À10% neutral buffered formalin (nbf) for morphology, or preserved in 95% non-denatured ethanol (EtOH) for DNA extraction. The ovoid TBF specimens with a relatively thick tegument (i.e., specimens of the first new species described below) were routinely heat-killed on glass slides using a butane hand lighter under little or no coverslip pressure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During July 2016, the viscera of 5 matamatas (C. fimbriata) from the Bele´n Market (3845 0 32.08 00 S, 73814 0 53.15 00 W), Iquitos, Peru (Amazon River), were examined opportunistically for blood fluke infections following previously published procedures (Roberts et al, 2016a(Roberts et al, , 2016b(Roberts et al, , 2016c(Roberts et al, , 2018a(Roberts et al, , 2018b(Roberts et al, , 2019 observed microscopically prior to fixation, fixed in 5À10% neutral buffered formalin (nbf) for morphology, or preserved in 95% non-denatured ethanol (EtOH) for DNA extraction. The ovoid TBF specimens with a relatively thick tegument (i.e., specimens of the first new species described below) were routinely heat-killed on glass slides using a butane hand lighter under little or no coverslip pressure.…”
Section: Methodsmentioning
confidence: 99%
“…1557310-1557319). Classification and anatomical terms for TBFs follow Roberts et al (2016aRoberts et al ( , 2016bRoberts et al ( , 2016c. Turtle scientific and common names follow van Dijk et al (2014), and higher classification of turtles follows Pereira et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…scripta (KY091666), the new species (KY091664) and Spirorchis picta (KY091665) plus six other TBFs in GenBank (Table 1). Methods for sequence alignment and phylogenetic tree construction follow Roberts et al (2016b).…”
Section: Present Studymentioning
confidence: 99%
“…scripta (KY091666), the new species (KY091664) and Spirorchis picta (KY091665) plus six other TBFs in GenBank (Table 1). Methods for sequence alignment and phylogenetic tree construction follow Roberts et al (2016b).The holotype and paratypes of the new species and vouchers of the redescribed species were deposited in the United States National Museum (USNM, Washington, D.C.) and the Institute of Parasitology (IPCAS, Biology Centre of the Czech Academy of Sciences, České Budějovice, Czech Republic). MacCallum, 1918, emended Figs.…”
mentioning
confidence: 99%
See 1 more Smart Citation